Cell-Based Interaction Analysis of ADAMTS Proteases and ADAMTS-Like Proteins with Fibrillin Microfibrils - Hubmacher, Dirk (Methods Mol Biol, 2020)
The extracellular matrix (ECM) is a composite biomaterial that serves as an anchor for cells and provides guidance cues for cell migration, proliferation, and differentiation. However, many details of the hierarchical ECM assembly process and the role of individual protein–protein interactions are not well understood. Here, I describe a cell-culture-based method that allows for determination of the ECM localization of recombinant ADAMTS proteases and ADAMTS-like (L) proteins in relationship to fibrillin microfibrils deposited by human dermal fibroblasts. The method can be readily adapted to study the localization of ECM components other than ADAMTS and ADAMTSL proteins to fibrillin microfibrils and other ECM networks.